Thermal conduction modulation for smart windows - Soon, Pei Pei (Nanyang Technological University, 2021)
As population increase globally, there is an ever-growing demand for energy, especially fossil fuels as it is the primary source of energy and these fossil fuels takes millions of years to be renewed. With greenhouse gasses emissions and global warming, there has been increased efforts since the 2000s to reduce energy consumption. More specifically, the use of smart glass windows started in the early 2000s to block light from passing through with the aim to reduce energy consumption by protecting occupants from weather fluctuations and increase air conditioning efficiency thus conserving energy used on heating and cooling. However, these technologies do not address the problem of heat transfer via radiation and conduction. Therefore, this research focuses on reducing thermal diffusivity through glass windows by promoting lateral heat diffusivity along the glass. During summer, the smart window allows the heat to be conducted across the glass and reduce heat passing through indoors to prevent heating up of the room and having the need to turn on cooling, similarly during winter, coldness can be prevented from passing through indoors so reliance on heating is reduced. This technology makes use of a cost-effective method by using carbon-based smart windows for modulation of heat transfer, in this research, graphene quantum dots films as well as metal-doped graphene quantum dots films are used.